A Highly Stable Ortho‐Ketoenamine Covalent Organic Framework with Balanced Hydrophilic and Hydrophobic Sites for Atmospheric Water Harvesting. Issue 24 (14th November 2022) - Chen, Liang‐Hui; Han, Wang‐Kang; Yan, Xiaodong; Zhang, Jiangwei; Jiang, Yuqin; Gu, Zhi‐Guo
Abstract: Atmospheric moisture is a sustainable clean water source that can solve the shortage of fresh water in arid areas. Herein a 2D covalent organic framework (COF‐ok) was reported as a promising porous sorbent for solar‐driven atmospheric water harvesting. COF‐ok with ortho ‐ketoenamine linkage was extremely stable in harsh environment, including in boiling water, strong acids and bases. Because of the balanced hydrophilic and hydrophobic sites in channels, COF‐ok showed a high water uptake of 0.33 g g −1 at a low relative humidity of 34 % featuring a characteristic S‐shaped water sorption isotherm with low regeneration temperature (∼45 °C) and excellent cyclic stability. A laboratory‐scale water harvesting system could collect water of 161 g kg −1 under sunlight. Abstract : Harvest of crops : The first example of ortho ‐ketoenamine COF (COF‐ok) with well‐balanced hydrophobic and hydrophilic sites was constructed by precise selection of building blocks. COF‐ok not only exhibited impressive water vapor adsorption capacity at low RH but also possessed remarkable photothermal conversion properties. Thus it was shown to be a promising candidate for achieving atmospheric water harvesting in arid regions.